Nitrogen use efficiencies, flows, and losses of typical dairy farming systems in Inner Mongolia - Qili, Moge; Zhao, Zhanqing; Bao, Junwei; Wu, Nier; Gou, Baomin; Ying, Ying; Bilige, Batu; Sun, Lin; Xue, Yanlin; Yang, Fuyu (Frontiers in Sustainable Food Systems, 2024)
Dairy farming is a notable source of nitrogen (N) emissions, impacting both atmospheric and aquatic ecosystems, thus necessitating a detailed analysis of nutrient dynamics to curtail nutrient wastage. However, N flow variability and its environmental ramifications differ markedly among dairy farms, and a holistic understanding of these differences is lacking in Inner Mongolia, the biggest dairy production province in China. Utilizing data from 187 dairy farms and employing the NUFER-farm model, this study assessed N flows, N use efficiency (NUE), and N losses across four predominant dairy farming systems in Inner Mongolia. These systems include traditional pastoral dairy farms (PF), smallholder dairy farms with croplands (SF), industrial landless farms (IDF), and coupled dairy cattle and cropland intensive farms (CDF). Our findings indicate considerable differences in N flows, NUE, and losses among the systems. On average, N deposition and N fertilizer were the primary N sources for PF and SF, respectively, whereas IDF and CDF derived over 90% of their N inputs from purchased feeds.PF and SF recycled all available manure N on-farm, whereas IDF and CDF recycled only about 36% of the total available manure N. N losses constituted 39%-72% of total N outputs, with ammonia emissions accounting for 68%-73% of total N losses across all farm types. Notably, PF had a higher N loss per kilogram of dairy product compared to other systems. Farm-level NUE ranged from 17% to 35%, with manure management practices showing significant variability, underscoring the potential for enhanced strategies to reduce N losses through improved manure treatment.